2016
DOI: 10.5858/arpa.2014-0644-oa
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleic Acid In Situ Hybridization Is a More Sensitive Method Than Immunohistochemistry in Detection of Thyroid Transcription Factor 1 and Napsin A Expression in Lung Adenocarcinomas

Abstract: Context.-TTF-1 and napsin A immunomarkers have a crucial role in differentiating lung adenocarcinoma from lung squamous cell carcinoma and in identifying a primary lung adenocarcinoma when working on a tumor of unknown origin.Objectives.-To investigate the diagnostic sensitivity of ribonucleic acid in situ hybridization (RNAscope) in the detection of expression of these biomarkers in lung adenocarcinomas and to compare RNAscope to immunohistochemical techniques.Design.-Both RNAscope and the immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Advances in RNA in situ hybridization (ISH) have revolutionized the ability to assess RNA expression in multiple specimen types, including formalin-fixed paraffin-embedded (FFPE) tissues (18,19). RNAscope technology provides single-molecule sensitivity and resolution, enabling quantification of specific RNA molecules at the single cell level (20).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in RNA in situ hybridization (ISH) have revolutionized the ability to assess RNA expression in multiple specimen types, including formalin-fixed paraffin-embedded (FFPE) tissues (18,19). RNAscope technology provides single-molecule sensitivity and resolution, enabling quantification of specific RNA molecules at the single cell level (20).…”
Section: Introductionmentioning
confidence: 99%
“…The recent emergence of highly sensitive RNA in situ hybridization (RISH) methodologies for use in formalin fixed paraffin embedded (FFPE) tissues has revolutionized our ability to examine RNA expression in tissues (32). The novel RISH assays provide a higher level of target sensitivity and specificity when compared with many immunostaining protocols (33). The increased specificity is achieved by requiring two separate oligonucleotides (Z-pairs) to hybridize near each other in order to generate a signal, and the increased sensitivity is achieved by having a series of these Z-pairs bind to the target as well has having a branched DNA amplification step prior to enzymatic amplification (32).…”
Section: Introductionmentioning
confidence: 99%
“…Our results in this study showed that the difference in the detection of UPK2 in UC between RNAscope (68.0%) and IHC (62.6%) was not significant and that there was a moderate positive correlation between RNAscope and IHC ( P < 0.001, R = 0.441) for the detection of UP II. However, RNAscope can improve TTF1 sensitivity by 10.0% and Napsin A sensitivity by 12.5% compared with those of IHC in lung adenocarcinomas [ 16 ]. In addition, compared with IHC, RNAscope improved both the specificity and sensitivity for GPC3 and GS by 20–30% in hepatocellular carcinoma [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNAscope is a more sensitive method than IHC for detecting thyroid transcription factor 1 (TTF-1) and Napsin A expression in primary lung adenocarcinomas. RNAscope may be considered for patients with clinically suspected lung adenocarcinoma but who are TTF-1- and Napsin A-negative as detected by IHC[ 16 ]. RNAscope improves Glypican3 (GPC3) and glutamine synthetase (GS) specificity and sensitivity by 20-30% in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%